PENINGKATAN HASIL BELAJAR MENULIS SURAT UNTUK TEMAN SEBAYA PADA MATA PELAJARAN BAHASA INDONESIA MELALUI PEMBELAJARAN OLAH PIKIR SEJOLI (OPS) SISWA KELAS IV SDN 1 COPER JETIS PONOROGO - Aminingsih, Murni (Educatio Vitae, 2016)
This research aims to determine the thinking process of the student at elementary school to solve indonesian lesson in terms of the mastery writing letters about sharing their experience for classmate. The subject are student fourth grade in Coper Elementary School who teached by the researcher. The determine can improving student ability and have good score. The researcher analyzed and interpreted the steps used bystudent with Olah Pikir Sejoli (OPS) method.The resultof this research indicated that the student can enjoying the lesson with this methods and can improving their score. Key Words: Mastery Concepts. Olah Pikir Sejoli (OPS)